1995
DOI: 10.1006/anbe.1995.0138
|View full text |Cite
|
Sign up to set email alerts
|

Nest switching and alloparental care in colonial white storks

Abstract: Abstract. White stork, Ciconia ciconia, chicks were observed to abandon their natal nests prior to independence and to be adopted by neighbouring foster parents in approximately 40% of broods at three breeding colonies. Nest switching coincided with a decrease in feeding rates by parents and an increase in aggression by siblings triggered by the flight exercises of nestmates, and mainly affected the eldest chicks in larger broods. Chicks that abandoned their natal nests moved into broods containing both fewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…The average number of eggs in Poland is 3.8, whereas the average number of nestlings is 2.9 (KOSICKI 2010). Nestlings hatch asynchronously and when they leave their nests they are no longer fed by their parents, starting from day 60 up to day 90 of their lives (REDONDO et al 1995). Since they breed in exposed open nests, severe weather conditions can directly affect nestling survival.…”
Section: Introductionmentioning
confidence: 99%
“…The average number of eggs in Poland is 3.8, whereas the average number of nestlings is 2.9 (KOSICKI 2010). Nestlings hatch asynchronously and when they leave their nests they are no longer fed by their parents, starting from day 60 up to day 90 of their lives (REDONDO et al 1995). Since they breed in exposed open nests, severe weather conditions can directly affect nestling survival.…”
Section: Introductionmentioning
confidence: 99%
“…For altricial and semi-precocial bird species, it has been proposed that adoptions are driven by offspring which receive inadequate parental care from their own parents, and therefore seek adoption into another brood (Pierotti & Murphy, 1987;Redondo et al, 1995;Brown, 1998). Although we have shown that precocial goslings chose foster families according to a characteristic of family quality, in order to determine whether adoption represents an active strategy by goslings it will be crucial to determine the potential benefits of adoption to the gosling.…”
Section: Are Adoptions Driven By the Gosling?mentioning
confidence: 83%
“…In species where parents actively feed offspring, the adoption and subsequent feeding of extra offspring often results in increased costs and decreased reproductive output of the foster parents (Pierotti & Murphy, 1987;Morris et al, 1991;Brown et al, 1995;Redondo et al, 1995). Under such circumstances, adoption represents an intergenerational conflict, where young are trying to obtain foster care which adults should be selected to avoid giving (Pierotti, 1988;Brown, 1998).…”
Section: Adoption As Inter-generational Conflict or Mutualism?mentioning
confidence: 99%
“…Alloparental care can also be manifested through replacement of one or both adults after eggs have been laid (Grubb et al, 1988) or through nest switching once young have learned to fly but remain dependent on parental care. Nest switching occurs most often in altricial and semialtricial species, and adoption usually occurs late in the development of the nestlings, resulting in short periods of alloparental care (Ferrer, 1993;Redondo et al, 1995). Postfledging adoption by nest switching has been documented in several avian species, including American Crows (Corvus brachyrhynchos; Schaefer and Dinsmore 1992), White Storks (Ciconia ciconia; Redondo et al, 1995), and Alpine Swifts (Apus melba; Bize and Roulin, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nest switching occurs most often in altricial and semialtricial species, and adoption usually occurs late in the development of the nestlings, resulting in short periods of alloparental care (Ferrer, 1993;Redondo et al, 1995). Postfledging adoption by nest switching has been documented in several avian species, including American Crows (Corvus brachyrhynchos; Schaefer and Dinsmore 1992), White Storks (Ciconia ciconia; Redondo et al, 1995), and Alpine Swifts (Apus melba; Bize and Roulin, 2006). In raptor species, post-fledging nest switching has been documented in Northern Goshawks (Accipiter gentilis; Kenward et al, 1993), Egyptian Vultures (Neophron percnopterus; Donazar and Ceballos, 1990), Ospreys (Pandion haliaetus; Poole, 1989;Gilson and Marzluff, 2000), Eagle Owls (Bubo bubo; Penteriani and Delgado, 2008), Spanish Imperial Eagles (Aquila adalberti; Ferrer, 1993), and Lesser Kestrels (Falco naumanni; Tella et al, 1997).…”
Section: Introductionmentioning
confidence: 99%